Students' Perceptions of TOEIC Training for Improving Listening and Reading Scores - Miftachudin, Miftachudin; Utari, Dian Asa; Puspandari, Lusia Eni; Erawati, Ika; Sari, Eka Dyah Puspita; Fathoni, Muhammad Rofiful (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2024)
This research aims to distinguish students' perceptions of the TOEIC training given by lecturers for final semester students to help them to achieve the passing grade determined by the campus as a graduation requirement. This research is a qualitative descriptive that revealed the reality of TOEIC training by analyzing relevant data. The selection of research subjects was carried out using a purposive sampling technique on students who had received TOEIC training. Data collection uses a closed questionnaire method which is applied to 186 students from 11 study programs who join TOEIC training. In depth interview was also conducted toward 30 students. The research questionnaire consists of 2 parts, namely: Perception of Learning Quality and Perception of benefits to TOEIC training. The result of this research shows that students have positive perception toward TOEIC training and they agree TOEIC training can improve their listening and reading score. Meanwhile, the interview reveals that students get benefit more from integrated skills approach using authentic material than just simulation and structured practices of TOEIC. This results give insights on future TOEIC Training about its effectiveness to improve students’ English proficiency as well as proposing the best method used in the future training of TOEIC.